At the service of the human community: an ethical approach to the international debt question - de Weck, Philippe ed. (UNIAPAC BrusselsBE)
Looks at the origin and originality of the Holy See's Document. Analyses the external causes (from the point of view of the debtor countries) of the debt crisis by looking at aspects such as the influence of interest rates; the influence of raw material prices; and the problems caused by protectionism. Also analyses the domestic causes (in relation to the debtor countries) of the debt crisis by looking at aspects such as inflation in the debtor countries and flight of capital. Reviews possible actions.